2021
DOI: 10.15381/rivep.v32i1.17690
|View full text |Cite
|
Sign up to set email alerts
|

Comportamiento productivo y valor nutricional de siete genotipos de trébol en tres pisos altitudinales de la sierra norte del Perú

Abstract: El objetivo del estudio fue evaluar el comportamiento productivo y el valor nutricional de siete genotipos de trébol en tres niveles de altitud (PA I: 2300-2800 msnm, PA II: 2801-3300 msnm y PA III: 3301-3800 msnm) de la sierra norte de Perú durante un año. Se instalaron cuatro genotipos de trébol blanco (Trifolium repens) y tres genotipos de trébol rojo (Trifolium pratense) en cada piso altitudinal (PA). Se evaluó el poder germinativo, peso y pureza de la semilla para asegurar la viabilidad del número de semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…23 cm; expressing the superiority of height in percentage, the cutting frequency of 45 days over 30 days is 31 %, and the cutting frequency of 60 days versus 45 days is 17 %, concluding that as the maturity stage of the plant advances, the increase in height continues, but with a gradual decrease, probably due to the genetic characteristics of the species, and the phenology and reproductive cycle of the plant. Comparing the values of the study with those found by Vallejos et al (2021) [28] of 21.95 cm, their results are lower, which may be due to soil and environmental conditions, among other factors, soil quality and management. During the two seasons of the year, no difference was found (p>0.05); this considers that the plant can grow, and there is no difference considering the effect of the season, taking the average of the three grazing moments.…”
Section: Plant Heightsupporting
confidence: 40%
See 3 more Smart Citations
“…23 cm; expressing the superiority of height in percentage, the cutting frequency of 45 days over 30 days is 31 %, and the cutting frequency of 60 days versus 45 days is 17 %, concluding that as the maturity stage of the plant advances, the increase in height continues, but with a gradual decrease, probably due to the genetic characteristics of the species, and the phenology and reproductive cycle of the plant. Comparing the values of the study with those found by Vallejos et al (2021) [28] of 21.95 cm, their results are lower, which may be due to soil and environmental conditions, among other factors, soil quality and management. During the two seasons of the year, no difference was found (p>0.05); this considers that the plant can grow, and there is no difference considering the effect of the season, taking the average of the three grazing moments.…”
Section: Plant Heightsupporting
confidence: 40%
“…The average of the values found in white clover Ladino variety for CP, according to the average of the three cutting frequencies (24.9 %), doubles that of ryegrass (12.5 %) and significantly exceeds weeds (15.4 %), highlighting the potential of this species (Pennisetum clandestinum) at 30 %, to enhance the quality of the diet [16] and the productivity of this association [23]. The CP of white clover at 30 and 45 days of cutting is higher than those found by Gierus et al (2012) [14] and Vallejos et al (2021) [28], but lower in NDF, suggesting the importance of timing in cutting. Likewise, ash concentration and DIVMS are in line with those obtained by Fonseca-López et al (2020) [32] and Vallejos et al, (2021) [28], further reinforcing the practical implications of these findings.…”
Section: Nutritional Valuementioning
confidence: 79%
See 2 more Smart Citations
“…Resultados similares fueron reportados por Boschi et al (2016) en estudios realizados en el campo experimental del Instituto Nacional de Semillas en Barros Blancos, Uruguay, en el que valores de comportamiento germinativo fueron: para trébol blanco de 93.6%, para trébol rojo de 92.1% y para alfalfa de 91.9%. Respuestas favorables, en el comportamiento germinativo, también fueron reportados por Vallejos et al (2021) en estudios realizados en la provincia de Santa Cruz, Cajamarca, Perú, en tres pisos altitudinales, en donde valores de comportamiento germinativo observados en Trifolium repens, cultivares Huía, Legacy, Ladino y Weka correspondieron al 81, 89, 58 y 70%, respectivamente, mientras que para el Trifolium pratense, cultivares Tuscan, Americano y Relish, valores de 98, 68 y 90%, respectivamente.…”
Section: Resultados Y Discusión Temperatura Y Humedad Del Suelo a Dos...unclassified